2021
DOI: 10.3390/ijms22094947
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Claudins: A New Tool to Study Tight Junction Structure and Function

Abstract: The tight junction (TJ) is a structure composed of multiple proteins, both cytosolic and membranal, responsible for cell–cell adhesion in polarized endothelium and epithelium. The TJ is intimately connected to the cytoskeleton and plays a role in development and homeostasis. Among the TJ’s membrane proteins, claudins (CLDNs) are key to establishing blood–tissue barriers that protect organismal physiology. Recently, several crystal structures have been reported for detergent extracted recombinant CLDNs. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…A recent article suggested that Barrier and Fence functions are independent of each other, indicating that in vivo ZO-1 is dispensable for the Barrier function [ 47 ]. The Barrier function can be impacted by the use of CLDN extracellular loop-peptides or other protein engineering strategies employing CLDNs [ 39 , 48 , 49 ]. We thus conclude that disrupting PPIs of CLDNs equates to disrupting cell–cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…A recent article suggested that Barrier and Fence functions are independent of each other, indicating that in vivo ZO-1 is dispensable for the Barrier function [ 47 ]. The Barrier function can be impacted by the use of CLDN extracellular loop-peptides or other protein engineering strategies employing CLDNs [ 39 , 48 , 49 ]. We thus conclude that disrupting PPIs of CLDNs equates to disrupting cell–cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of the chCLDN is to bind to native CLDN proteins and disrupt their ability to bind naturally with other CLDNs (see Figure 1a). To create this protein, we utilized the method outlined by Taylor et al, 2021. After collecting the DNA sequences of our CLDN of interest, the sequences corresponding with the transmembrane regions of the protein were substituted for a synthetic protein (referred to hereafter as 836), allowing it to maintain the general CLDN structure while preventing binding within the cell membrane. By doing so, the chCLDN has the ability to bind to specific types of CLDNs and interrupt their native interactions across the TJ.…”
Section: Methods Chimeric Claudin Synthesismentioning
confidence: 99%
“…The human genome contains 23 different types of CLDNs which play an important role in creating a structure called the tight junction (TJ). This structure enables neighboring cells to adhere to one another (Gamero-Estevez et al, 2018;Taylor et al, 2021) and is essential for numerous important steps in development including proper NT folding (Baumholtz, Gupta, et al, 2017;El Andalousi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we recombinantly expressed the two extracellular immunoglobulin domains of JAM-A. We used Maltose Binding Protein (MBP) as a fusion partner to allow for the generation of high yield of proteins, and to maintain consistency with our previous work [14,47,[70][71][72]. The pET28-MBP-JAM-A (Figure S3) plasmid was expressed in the SHuffle T7 bacterial strain to allow for the proper folding, disulfide formation and cytoplasmic expression of the JAM-A extracellular protein [45].…”
Section: Expression System Cloning and Purification In E Colimentioning
confidence: 99%